Married Women and the Law - Tim Stretton, Krista J. Kesselring (McGill-Queen's University Press, 2014)
Taken from the records of the court of Common Pleas, the illustration on this volumeâ€™s frontispiece depicts Queen Mary I holding the sceptre of power alongside her husband, King Philip. As a â€œfemale kingâ€ as well as a wife, Mary was exceptional in many ways, but her brief tenure as a married sovereign highlights issues surrounding women, marriage, power, and legal personhood that shaped the lives of many and that constitute the subject of this volume. When Mary became Englandâ€™s first anointed queen regnant in 1553, most people proved willing to accept that her physical sex posed no hindrance to her taking the throne. A female ruler was unprecedented, but thinkable. Having most recently been ruled by a young boy king, people had practice separating the â€œkingâ€™s two bodies,â€ the body natural and the body politic.1 Maryâ€™s possession of the crown freed her from such legal disabilities as applied to women in general. As the Act Concerning Regal Power (1554) declared, the kingly office, â€œinvested either in Male or Female,â€ was to be â€œtaken in the one as in the other.â€2 But when Mary began to talk of marriage, matters complicated. In England, a woman could rule; but could a wife? English law was unusual, not only in allowing a woman to inherit the highest position in the land, but also in the degree to which it subsumed a married womanâ€™s legal self in her spouse. Was the crown in any sense subject to the common law rules of â€œcoverture,â€ which worked to allow a husbandâ€™s legal personality to cover that of his wife?Maryâ€™s carefully penned marriage articles suggested some of the challenges women usually faced upon marriage: they asked the prospective groom to give up usual husbandly rights and to agree that he would not take his wife or their children from the country, or remove any jewels, ordnance, or other property, without her permission. It stipulated that while Philip would be called King, he â€œshall permit and sufferâ€ Mary to reign as Queen. Only later did members of parliament somewhat audaciously add a proviso that declared her to be as much â€œsole Queenâ€ after the marriage as before, simply setting aside the usual legal effects of marriage.3 Philip deemed the whole agreement deeply dishonourable, forced upon him against his will.4 Related discussions characterized the unsuccessful marriage negotiations of Maryâ€™s half-sister Elizabeth, who ultimately and notoriously refused to wed; similar legal clauses found their way into the marriage documents of Queen Mary II, Queen Anne, and then Queen Victoria almost 300 years later. Each of these royal marriages forced contemporaries to consider the nature of wedlock and to establish exceptions that allowed the powers of a monarch to trump the disabilities of a wife, who in any other circumstance was legally subservient to her husband. The need for such exceptions, even for women of such privileged status, and over such a span of time, highlights the strength of coverture â€“ as does the ability of coverture to persist despite these and many other deviations from its rules.